1991
DOI: 10.1002/(sici)1097-4571(199105)42:4<233::aid-asi1>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of science by combined co-citation and word analysis. I. Structural aspects

Abstract: The claim that co-citation analysis is a useful tool to map subject-matter specialties of scientific research in a given period, is examined. A method has been developed using quantitative analysis of content-words related to publications in order to: (1) study coherence of research topics within sets of publications citing clusters, i.e., (part of) the "current work" of a specialty; (2) to study differences in research topics between sets of publications citing different clusters; and (3) to evaluate recall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
208
0
7

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(216 citation statements)
references
References 27 publications
1
208
0
7
Order By: Relevance
“…[18][19][20][21][22][23][24][25] After the 90's, new methods of information retrieval and new techniques for the analysis, visualization and spatial positioning of information (well reviewed by Börner, Chen and Boyack 26 ), studies based on techniques for visualizing the structure of small scientific domains begin to proliferate. So, for instance, Braam, Moed and van Raan 27,28 propose the combined use of cocitation with co-word analysis for the generation of science maps, emphasizing their structure and dynamic aspects. Lin, Soergel and Marchionini 29 develop a Self-Organizing Map (SOM) that represents the semantic relationships among documents and can be used as a bibliographic interface for the retrieval of online information.…”
mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] After the 90's, new methods of information retrieval and new techniques for the analysis, visualization and spatial positioning of information (well reviewed by Börner, Chen and Boyack 26 ), studies based on techniques for visualizing the structure of small scientific domains begin to proliferate. So, for instance, Braam, Moed and van Raan 27,28 propose the combined use of cocitation with co-word analysis for the generation of science maps, emphasizing their structure and dynamic aspects. Lin, Soergel and Marchionini 29 develop a Self-Organizing Map (SOM) that represents the semantic relationships among documents and can be used as a bibliographic interface for the retrieval of online information.…”
mentioning
confidence: 99%
“…Janssens et al (2008) gave an overview of studies published since the seminal work of Braam et al (1991), which have shown that hybrid clustering methods that incorporate text and citation information can outperform clustering methods that use only one of these components, and they proposed a new hybrid method that outperforms both. Another form of hybrid clustering combines text-based document similarities with author similarities; this can be used for example for expert finding (Tho et al, 2007).…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…We encourage interactive model construction and labelling (as in Fortuna et al, 2006), leverage citation and textual information (as in Braam et al, 1991;Chen, 2006), and build on word profiles for characterising the content of document clusters (as in Braam et al, 1991;Chen, 2006;Fortuna et al, 2006;Janssens et al, 2008). In addition, we extend these functionalities by helps for personal productivity (storage) and sharing with others.…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 2 more Smart Citations